1. The problem statement, all variables and given/known data Problem 1: Solve log(x^3) = (log(x))^2 for x. Note, there are two solutions, A and B, where A < B. A = ? B = ? Problem 2: Rewrite the expression 2log(x)-2log(x^2+1)+4log(x-1) as a single logarithm log A. A = ? 2. The attempt at a solution Problem 1 Attempt: I might be able solve this graphically by plotting y1 = log(3^x) and y2 = (log(x))^2 and finding the points of intersection. However, I'd like to do this by hand, if possible! Would I start by raising both sides to e? e^log(x^3) = e^(logx)^2 then x^3 = e^2 then x = (e^2)^(1/3) x = e^(2/3) x = 1.947734 Wolfram-alpha says otherwise :( and there are supposed to be 2 solutions. I only got one D: Problem 2 attempt: Okay, I tried using properties of logarithms here. 2log(x)-2log(x^2+1)+4log(x-1) 2log(x) - 8*log(x^3 - x^2 + x - 1) <------- Since the 2 logs are added, you can multiply the insides of the logs together, right? 16*log(x/(x^3-x^2+x-1)) <------------ Since the 2 logs are subtracted, you can divide them, right?